Mechanical and hydrological time-dependent properties of granulated blast furnace slag-sand mixture in soft ground improvement - T. Sakata; N. Yasufuku; R. Ishikura; A. Alowaisy (Lowland Technology International, 2018)
Every year about 20 million tons of Granulated Blast Furnace Slag (GBFS) are produced as a manufacturing byproduct. GBFS is mainly utilized in cement production accounting for 70% of the total utilized weight, while the geotechnical engineering applications accounts for 2%. Therefore, finding innovative utilization methods is a necessity. It was reported that the GBFS can be used as substitutive material in sand compaction pile (SCP) method. This study aims at evaluating the time-dependent mechanical, hydrological and chemical properties of the GBFS and the GBFS-sand mixtures. It was found that for early hydration stage, the hydrological and mechanical properties of the GBFS depends on the microstructure of the material, while the generation of the calcium silicate hydrate can be neglected. On the other hand, for longer curing time the influence of the calcium hydrate silicate generation becomes significant. Finally, it was concluded that mixing the GBFS with sand is a simple efficient way to control the time dependent mechanical, hydrological and chemical properties of the GBFS, however, the combined effect of the hydration reaction rate and the void ratio developments in response to the mixing ratio and the curing time should be properly considered to optimize utilizing the GBFS.